Distribution of Giardia lamblia Among local and Displaced Children in Kirkuk City - M. M. Bakr, M; Sh. A. Mohammad; M. A. Kadir (Tikrit Journal of Pure Science)
The aim of this study was to show the distribution of Giardia lamblia infection among local and displaced children in Kirkuk city, and its effect on some hematological parameters Haemoglobin (Hb), Packed cell volum (PCV) White Blood Cell Counts (WBCc). The stool samples were examined by direct wet mounts techniques, concentration and ELISA techniques. Blood sample were collected from each child and some hematological parameters were estimated for them. The overall rate of Giardia lamblia infection in displaced children 21.5% was higher than local ones 10.53% . The prevalence of infection males 15.64% was higher than females 12.01% in both local and displaced children . The hemoglobin value among local children was significantly lower than displaced children. while the PCV value among local children was significantly higher than displaced ones. The rate of WBC in local and displaced children was increased slightly, its value in local children 10.13% and in displaced children10.30%. Its concluded that the distribution of Giardia lamblia was high in both local and displaced children. The rate of infection in displaced children was higher than local children